A STUDY OF FIGURATIVE LANGUAGE FOUND IN BRUNO MARS’ SONGS ON DOO WOPS & HOOLIGAN ALBUM - RITONGA, ANGGI MEIRIANA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : Stylistics, Figurative Language, Bruno Mars’ Doo Wops & Hooligan Album. This research deals with figurative language employed in Bruno Mars’ songs on Doo Wops & Hooligan album. There are two problems to answer in the analysis. First is what figurative languages of the song are found in Bruno Mars’ Doo Woops & Hooligan album. For the second one is what messages of the song are found in BrunoMars’ Doo Woops & Hooliganalbum. The objectives of this study are to find out what figurative languages and messages of the song that are found in Bruno Mars’Doo Woops & Hooligan album. This study uses qualitative approach while the research design is content or document analysis. The data source used in this study is the lyrics of the 10 songs of Bruno Mars in Doo Wops & Hooligan album. This study uses the theory of figurative language by Kennedy and Gioia (2005). The data are 108sentences containing figurative languages in the lyrics found in Bruno Mars’ songs on Doo Wops and & Hooligan album. Those figurative languages are divided into 4 personifications, 10 similes, 35 metaphors, 28 hyperboles, 26 synecdoches, 4 apostrophes, 1 irony. The figurative language that is mostly used in this album is metaphor. The song writer uses the figurative language to add some elegance to the song. There are also messages of each song that were shown by the use of figurative language. The writer suggests that the future writers understand the theory of stylistics, especially about figurative language and its meaning to understand the contents of atext and also its messages and functions. Second is they could use another theory to make their study different from the writer’s. Third, if they want to conduct a studythat is related to the written media, it is suggested that they should decide the objectwell so it will not make any trouble when the study is going on.